THE IMPACT OF THE COVID-19 PANDEMIC ON THE IMPLEMENTATION OF COMMERCIAL CONTRACTS REVIEWED IN CIVIL LAW - Rizkia, Nanda Dwi; Arzuna, Pit; Winarsasi, Putri Ayi; Utama, Liza; Mustikowati, Endang; Huda, Khoirul (Fakultas Hukum Universitas Kristen Indonesia Paulus, 2024)
The COVID-19 epidemic has significantly altered the execution of business contracts, especially with regards to the renegotiation of duties and the use of force majeure. In light of the difficulties brought on by the pandemic, this research examines the ways in which Indonesian civil law, as codified in the Civil Code, deals with matters such as contract modifications. Studying both primary and secondary sources of law is at the heart of the normative legal research methodology. It is frequently necessary to renegotiate contracts in order to modify rights and responsibilities, since the study's findings demonstrate that force majeure does not necessarily apply to all contracts in a pandemic scenario. Findings from this research stress the need for more lenient laws to resolve contract disputes in the midst of the epidemic and for more transparent rules to govern the use of force majeure.